The effect of emotional intelligence levels of intensive care and clinical nurses on psychological resilience - Gümüş, Cemile; Tülay Yılmaz Bingöl; Nermin Gürhan (Nursing and Health Sciences Journal (NHSJ), 2025)
Nurses must have communication skills, empathy, and the ability to deal with the challenges of patient care effectively. Emotional intelligence and psychological resilience are skills that nurses can develop in adapting, collaborating, and providing quality patient care. This study aims to determine the effect of the emotional intelligence levels of intensive care and clinical nurses on their psychological resilience levels. In this descriptive cross-sectional study, 252 intensive care and ward nurses met the study sample. "Personal Information Form," "Emotional Intelligence Scale," and "Adult Resilience Measure" were used as data collection tools in the research. The nurses' "total emotional intelligence" average was found to be high at 139.060±24.129 (min=33 and max=180). The "psychological resilience total" score average was low at 86.774±10.648 (min=55 and max=105). It has been found that emotional intelligence affects psychological resilience in nurses. The psychological resilience of nurses working in intensive care units was lower than that of clinical nurses. Healthcare organizations need to increase the well-being of nurses in complex working environments with intervention programs emphasizing emotional intelligence and psychological resilience. The results of this study are important to encourage the improvement of nurses' well-being.